Hubungan Antara Faktor Penghambat Dengan Penerapan Manajemen Keselamatan Kerja Di Rumah Sakit X - Prasetia, Aisya Amalia Putri; Kurniawan, Afif; Tjokro, Silvia Haniwijaya; Fajriyah, Novita (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2025)
Background: Work safety in hospitals is still a problem. With so many dangers occurring, efforts need to be made to reduce or even eliminate hazard controls. For hospital accreditation, work safety must be managed well. Aims: The aim of this research is to reduce inhibiting factors in the implementation of this system so that hospitals can be managed well. Methods: This research design is quantitative with the Cross Sectional method, the research sample consists of 44 respondents. Results: Fisher’s test results show that there is no correlation between K3 and work capacity, workload and work environment. The majority of female respondents in hospital x (66%), had a bachelor;s degree (66%), and had worked for more than 5 years (55%). Conclusion: There is no significant relationship between work capacity, workload, work environment and work safety in hospital x.